Quality of life in patients with craniofacial anomalies: personal experience and review of literature - Jula Cazacu, Corina; Jula, Ciprian Radu; Grammatikis, Efstathios; Șapte, Elena (Medicine and Pharmacy Reports, 2026)
Background. Craniofacial anomalies, particularly cleft lip and palate affecting 1 in 500 to 1 in 2,500 live births globally, exert profound influences on physical function, psychological well-being, and social integration throughout the entire life. While surgical advances have improved outcomes, the long-term impact on the quality of life remains incompletely understood, necessitating comprehensive evaluation of psychosocial outcomes following primary surgical repair. Methods. We conducted a cross-sectional comparative study evaluating 85 pediatric patients aged 4-7 years with surgically repaired non-syndromic cleft lip and/or palate and their caregivers, compared to 90 age-matched healthy controls. All patients underwent standardized surgical repair with minimum 24-month postoperative follow-up. Quality of life was assessed using the validated KINDL questionnaire administered to both children and parents, measuring physical well-being, emotional well-being, self-esteem, family relationships, friendships, and school functioning. Statistical analysis employed independent-samples t-tests and chi-square tests with significance set at p < 0.05. Results. Children with cleft conditions demonstrated overall quality of life scores comparable to healthy controls (82.15 ± 14.72 vs 83.78 ± 16.72, respectively; 1.9% difference, not statistically significant). However, self-esteem scores were significantly lower in the cleft group (78.17 ± 24.79 vs 83.49 ± 22.17, p = 0.036). Parental assessments yielded high overall scores (80.38 ± 12.41) but identified significant concerns in self-esteem (72.41 ± 16.82) and infirmity perception (72.15 ± 17.67) (both p < 0.01). Age-stratified analysis revealed that children requiring reinterventions and older children (6-7 years) demonstrated greater family-related quality of life concerns. Conclusions. While children with surgically repaired cleft lip and/or palate achieve overall quality of life outcomes comparable to healthy peers, persistent self-esteem deficits indicate ongoing psychosocial challenges requiring comprehensive multidisciplinary intervention. These findings emphasize the need for holistic care approaches that integrate psychological support, targeted therapies, and family counseling to optimize both functional and psychosocial outcomes beyond primary surgical repair.